2018
DOI: 10.1002/we.2272
|View full text |Cite
|
Sign up to set email alerts
|

Prospective challenges in the experimentation of the rain erosion on the leading edge of wind turbine blades

Abstract: Developments in the wind industry reveal intricate engineering challenges, one of them being the erosion on the leading edge of the wind turbine blades. In this review work, the main issues for the wind industry in the experimentation with respect to erosion are examined. After a historical and general overview of erosion, this review focuses on the rain erosion on the leading edge of the wind turbine blades giving prominence to (1) the rain simulations, (2) experimental erosion facilities, and (3) variables t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 83 publications
(145 reference statements)
0
47
0
Order By: Relevance
“…Thus, the leading edge actually comprises several layers of the main structural composite material (and thickening materials) plus coatings (Mishnaevsky Jr. et al, 2017). Impact fatigue caused by collision with rain droplets and hail stones is a primary cause of WT blade LEE (Bech et al, 2018;Bartolomé and Teuwen, 2019;Zhang et al, 2015). Although rain droplets fall at only modest velocities (typically ≤ 10 m s −1 , see details below), the tip of WT blades rotate quickly (50-110 m s −1 ); thus the net closing velocity and kinetic energy transfer are large.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Thus, the leading edge actually comprises several layers of the main structural composite material (and thickening materials) plus coatings (Mishnaevsky Jr. et al, 2017). Impact fatigue caused by collision with rain droplets and hail stones is a primary cause of WT blade LEE (Bech et al, 2018;Bartolomé and Teuwen, 2019;Zhang et al, 2015). Although rain droplets fall at only modest velocities (typically ≤ 10 m s −1 , see details below), the tip of WT blades rotate quickly (50-110 m s −1 ); thus the net closing velocity and kinetic energy transfer are large.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Despite the possible diverse wind turbine configurations, the horizontal-axis wind turbine (HAWT) with three blades is the most common design. The blades mainly consist of two shells that are bonded with adhesive and made of composite material [6,34]. The two shells form an airfoil shape that has a leading and a trailing edge as shown in Figure 2.…”
Section: Blade Design and Materialsmentioning
confidence: 99%
“…Moreover, one nozzle is often used with rotating disk rigs, which helps in quantifying the exact number of droplets impacting the sample at each revolution [121]. As noted by Bartolomé and Teuwen [34], rotating devices are inherently incapable of replicating the movement of the turbine blade during rainfall impacts. The interaction between the raindrop and the wind turbine blades principally depends on the position of the blade during rotation.…”
Section: Testing Facilitiesmentioning
confidence: 99%
“…LEE is caused by repeated bombardment, primarily by raindrops and particulate matter, hail, ice, salt, and UV, which lead to erosion and an increase in surface roughness. [3][4][5][6][7][8] The increase in roughness that results from this erosion process creates extra resistance to the flow over the surface, which impairs the aerodynamic performance of a blade in the form of increased drag and thus potentially premature stall, reducing WTG efficiency and decreasing the generating capacity of a windfarm. 1,5,7,8 This consequently reduces AEP and ROI.…”
mentioning
confidence: 99%
“…What was also clear was that the reduction in drag was very aerofoil dependent. Sareen et al 15 looked at Reynolds numbers from 1 to 1.85×10 6 and also adjusted where the tape ended over the suction side of the aerofoil. As with Giguére and Selig, 14 they found that the further the tape extended, this case to a maximum of 30% chord, the smaller the increase to the drag, again attributed to the backward step of the tape influencing boundary layer transition.…”
mentioning
confidence: 99%